RHPMAN: Replication in Highly Partitioned Mobile Ad Hoc Networks - Ke Shi; Hongsheng Chen (International Journal of Distributed Sensor Networks)
Accessing data in mobile ad hoc networks is a challenging problem, which is caused by frequent network partitions due to node mobility and due to the impairments of wireless communications. The partitioning pattern is studied by examining the statistics of network partitions for a number of mobility models. Then the relation between the network partitioning pattern and the effectiveness of the data replication scheme is established. Based on these results, a novel replication scheme, RHPMAN (replication in highly partitioned mobile ad hoc network), taking into account the fact that the network is often partitioned in smaller portions, enjoying only intermittent connectivity thanks to mobile nodes traveling across partition, is proposed. In RHPMAN, data items are replicated to the nodes with rather stable neighboring topology and with enough resources. A semiprobabilistic data disseminating protocol is employed to distribute the replicas and propagate the updates, which can identify the potential mobile nodes traveling across partitions to maximize data delivery. To maintain replica consistency, a weak consistency model is utilized to ensure that all updates eventually propagate to all replicas in a finite delay. Simulation results demonstrate that RHPMAN can achieve high data availability with low overhead.